Commitment and trust in achieving financial goals of strategic alliance: Case in Islamic microfinance. Issue 4 (11th November 2014) - Wahyudi, Imam
Abstract : Purpose: – This paper aims to illustrate theoretically and empirically the decision and result of strategic alliance between baitul maal wa tamwil (BMT) and Islamic banks as a relationship based on trust, mutual-trustworthiness and commitment. This paper also identifies the basic criteria for the resilience of a strategic alliance, the challenges and the barriers in a strategic relationship along with managerial and operational implications. Design/methodology/approach: – In this study, we have chosen to use the confirmatory approach through a structured questionnaire by means of field survey to 131 BMT spread throughout Central Java and Yogyakarta. From the total sample, 89 BMT fulfilled the sampling criteria, that is: has operated for a minimum of two years and does not experience any financial difficulties during those two years; has done a financing contract with an Islamic bank; channels some of its funds to micro, small and medium enterprises; and is in the form of a cooperative, and not a micro financial institute. Data treatment uses the method of listwise deletion. Data analysis uses equation model with the software LISREL version 8.80. To validate the result of data analysis, we have also run a focus group discussion with Directorate of Syariah Banking, Bank of Indonesia, and in-depth interviews with BMT parent cluster (Inkopsyah). Findings: – This research shows that commitment contributes positively in achieving the financial goals of an alliance. Coordination and initial agreement has a positive and significant influence in forming commitment from BMT and trust from Islamic banks. Other than coordination and initial agreement, the trust given by Islamic banks also came from the social capital owned by BMT. Originality/value: – The trust and commitment will assist the building of strategic alliance between Islamic banks and BMT. Apart from financial purposes, the alliance between the two will also encourage natural knowledge-sharing.